2017
DOI: 10.1021/acs.jpcc.6b11423
|View full text |Cite
|
Sign up to set email alerts
|

Large-Scale Synthesis of Graphene-Like MoSe2 Nanosheets for Efficient Hydrogen Evolution Reaction

Abstract: Two-dimensional (2D) materials have attracted great attention by researchers due to their fascinating properties and promising applications. However, the synthesis methods for few layers are usually difficult to expand to large area applications because of their low yield. In this paper, graphene-like MoSe2 nanosheets are successfully and scaleable synthesized by a facile and low-cost hydrothermal method under the synergy of PVP and graphene. The ultrathin MoSe2 nanosheets are typically 1–3 layers, which are c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(45 citation statements)
references
References 52 publications
4
40
0
Order By: Relevance
“…The MS-6 sample had at ypical flower-like morpholo-gy (Figure 5a), in whichas ingle MoSe 2 nanosheet was stacked into ultrathin few-layered assembliesw ith at hickness of approximately 5nm( Figure S2). [43] This was in agreement with the XRD patterns,i nw hich the peak of the (0 02)p lanes shifted to al ower degree. [43] This was in agreement with the XRD patterns,i nw hich the peak of the (0 02)p lanes shifted to al ower degree.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…The MS-6 sample had at ypical flower-like morpholo-gy (Figure 5a), in whichas ingle MoSe 2 nanosheet was stacked into ultrathin few-layered assembliesw ith at hickness of approximately 5nm( Figure S2). [43] This was in agreement with the XRD patterns,i nw hich the peak of the (0 02)p lanes shifted to al ower degree. [43] This was in agreement with the XRD patterns,i nw hich the peak of the (0 02)p lanes shifted to al ower degree.…”
Section: Resultssupporting
confidence: 88%
“…The HRTEM images of the crosssection at the internal area of the MS-6 assemblies (Figure 5b,c) revealed that the spacing between two adjacent monolayers was approximately 0.742 nm, which was an indication of highly expanded (0 02)p lanes of 1T-MoSe 2 . [43] This was in agreement with the XRD patterns,i nw hich the peak of the (0 02)p lanes shifted to al ower degree. Furthermore, the interplanar spacing of the MS-6 was 0.239 nm, corresponding to the (1 03)p lanes of hexagonal MoSe 2 (Figure 5c).…”
Section: Resultssupporting
confidence: 88%
“…To date, most of the works adopted the current density of 10 mA cm −2 as the benchmark to compare the HER performance, and there is no work on HER comparison of MoSe 2 at larger current density such as100 mA cm −2 . To realize large current HER, apart from the phase engineering, morphology engineering is indispensable . Power form is usually not suitable for large current HER due to the use of insulating binders and detach from substrate arising from bubble‐striking effect.…”
mentioning
confidence: 99%
“…Among the TMDs (MX 2 where M = Mo, W; X = Se, S) MoSe 2 is considered as a superior active electrocatalyst because both Mo and Se edges are active for H + binding [25]. Various groups have recently probed MoSe 2 [6], alloys of MoSe 2 with S [9], S-doped MoSe 2 [22], vertically aligned MoSe 2 [26], nanohybrid of MoSe 2 [32], ultrathin MoSe 2 NSs decorated on graphene and carbon fibre as electrocatalysts for HER [33,34]. Recently, Chen et al and Lee et al used Mo/MoSe 2 as efficient CE in DSSCs [10,11].…”
Section: Introductionmentioning
confidence: 99%